Physical activity and the ‘pediatric inactivity triad’ in children living with chronic kidney disease: a narrative review - Thomas J. Wilkinson; Lauren L. O’Mahoney; Patrick Highton; Joao L. Viana; Heitor S. Ribeiro; Courtney J. Lightfoot; Ffion Curtis; Kamlesh Khunti (Therapeutic Advances in Chronic Disease, 2022)
The ‘paediatric inactivity triad’ (PIT) framework consists of three complex inter-related conditions that influence physical inactivity and related health risks. In those living with chronic kidney disease (CKD), a multi-factorial milieu of components likely confound the PIT elements, resulting in a cycle of decreased physical functioning and reduced physical activity. In this review, we explore and summarize previous research on each of the three principal PIT components (exercise deficit disorder, dynapenia, and physical illiteracy) in the pediatric CKD population. We found those living with CKD are significantly physically inactive compared to their peers. Physical inactivity occurs early in the disease process and progressively gets worse as disease burden increases. Although physical activity appears to increase post-transplantation, it remains lower compared to healthy controls. There is limited evidence on interventions to increase physical activity behaviour in this population, and those that have attempted have had negligible effects. Studies reported profound reductions in muscle strength, physical performance, and cardiorespiratory fitness. A small number of exercise-based interventions have shown favourable improvements in physical function and cardiorespiratory fitness, although small sample sizes and methodological issues preclude the generalization of findings. Physical activity must be adapted and individualized to the needs and goals of the children, particularly those with acute and chronic medical needs as is the case in CKD, and further work is needed to define optimal interventions across the life course in this population if we aim to prevent physical activity declining further.